Rapunzel vs. Frankenstein : a graphic novel - Powell, Martin, 1959-; Lozano, Omar (North Mankato, Minnesota : Stone Arch Books, 2020)
When Rapunzel discovers Dr. Frankenstein's castle she is just looking for some medicine for her cold, but contact with one of his chemicals causes her hair to grow and come alive, along with the clay 'monster' in his lab; Frankenstein is horrified at his own success, and it is up to Rapunzel to convince him and the townspeople that neither she nor Clay is really a monster--and that living hair has some advantages.
2.8
3-6
GN550L
Keywords: Frankenstein, Victor -- (Fictitious character) -- Comic books, strips, etc. -- Juvenile fiction; Monsters -- Comic books, strips, etc. -- Juvenile fiction; Characters and characteristics in literature -- Comic books, strips, etc. -- Juvenile fiction; Frankenstein, Victor -- (Fictitious character) -- Fiction; Monsters -- Fiction; Characters in literature -- Fiction; Cartoons and comics; Fairy tales; Monster fiction; Graphic novels; Comics (Graphic works)